1981
DOI: 10.1093/ajcn/34.7.1338
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ascorbic acid, vitamin B6, vitamin B12, and folic acid supplementation on the breast milk and maternal nutritional status of low socioeconomic lactating women

Abstract: In this double-blind study, the effects of ascorbic acid, vitamin B6, vitamin B12, and folate supplementation on the maternal nutritional status and vitamin content of breast milk in 16 low socioeconomic lactating women were studied. Nine subjects were administered a commercial multivitamin-multimineral supplement and seven were given placebos. Milk samples were collected four times per day at 4-h intervals from 5 to 7 and 43 to 45 days postpartum. Fasting blood samples were taken from all mothers at the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 24 publications
0
37
0
2
Order By: Relevance
“…When comparing infants from multivitamin-supplemented mothers to infants from non-multivitamin-supplemented mothers, we found a major effect in serum vitamin B12 at 6 weeks that was sustained through 6 months of age. Observational studies had suggested that the vitamin B12 status of newborns is strongly associated with that of their mothers (Bjorke Monsen et al, 2001) and that correction of deficiencies through vitamin B12 supplementation among presumably HIV-uninfected mothers resulted in greater B12 concentrations in breast milk (Thomas et al, 1979(Thomas et al, , 1980Sneed et al, 1981). It has been described that vitamin B12 concentrations decrease in the newborn during the first 6-8 weeks (Bjorke Monsen & Ueland, 2003); our results suggest that maternal supplementation with multivitamins at multiples of the recommended dietary allowance (RDA) in USA could prevent such a decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing infants from multivitamin-supplemented mothers to infants from non-multivitamin-supplemented mothers, we found a major effect in serum vitamin B12 at 6 weeks that was sustained through 6 months of age. Observational studies had suggested that the vitamin B12 status of newborns is strongly associated with that of their mothers (Bjorke Monsen et al, 2001) and that correction of deficiencies through vitamin B12 supplementation among presumably HIV-uninfected mothers resulted in greater B12 concentrations in breast milk (Thomas et al, 1979(Thomas et al, , 1980Sneed et al, 1981). It has been described that vitamin B12 concentrations decrease in the newborn during the first 6-8 weeks (Bjorke Monsen & Ueland, 2003); our results suggest that maternal supplementation with multivitamins at multiples of the recommended dietary allowance (RDA) in USA could prevent such a decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among presumably HIV-uninfected women have shown that supplementation with vitamins A and B12 during early lactation increases the concentrations of nutrients in breast milk and results in improved vitamin status of infants during the first 6 months (Thomas et al, 1979;Sneed et al, 1981;Stoltzfus et al, 1993;Roy et al, 1997;Muslimatun et al, 2001;Bahl et al, 2002). Therefore, it has been proposed that vitamin supplementation to lactating mothers may be an efficient way to improve the vitamin status of both mothers and infants (Stoltzfus et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that lactation does not affect the level of folate (Cole et al, 1974;Thomas et al, 1980;Ek, 1983). A possible B12 depletion during lactation is apparently less common than folate depletion (Shapiro et al, 1965;Sneed et al, 1981;Dostalova, 1984;Donangelo et al, 1989;Keizer et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Several investigations show an increased risk of suboptimal folate status (Matoth et al, 1965;Donangelo et al, 1989;Lehti, 1989;Ramlau-Hansen et al, 2003;Villalpando et al, 2003) and a reduction in folate stores during the lactation period (Shapiro et al, 1965;Tamura et al, 1980;Butte et al, 1981;Sneed et al, 1981;Smith et al, 1983;Dostalova, 1984;Bruinse et al, 1985;Bates et al, 1986;Salmenpera et al, 1986;Keizer et al, 1995;Mackey and Picciano, 1999) in women with no folic acid supplementation and with a diet insufficient in folate. Others have shown that lactation does not affect the level of folate (Cole et al, 1974;Thomas et al, 1980;Ek, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Further, colostrum is rich in fat-soluble vitamin A, carotenoids, and vitamin E. The average vitamin A level on the third day can be three times that of mature milk. Similarly, carotenoids in colostrum may be ten times the level in mature milk, and vitamin E may be two to three times greater than in mature milk (35).…”
Section: Non-enzymatic Antioxidant In Human Milkmentioning
confidence: 99%